El “concepto hermenéutico”. Una interpretación del juicio estético puro kantiano desde Heidegger - Moreno Tirado, Guillermo (Con-Textos Kantianos. International Journal of Philosophy, 2020)
This paper presents a foundation of the intellectual artefact “hermeneutic concept” based on an interpretation of the “Deduction of pure aesthetic judgment” of the third Kantian Critique. Since the denomination for this artefact and the first characterization is found in a Heidegger course, I will proceed by offering the context of discussion in which it arises, namely, the Heideggerian interpretation of the Kantian transcendental schematism. Then, I will give the interpretation of the Deduction that allows us the foundation of the “hermeneutic concept” and, once the route of that foundation is completed, two reading hypothesis will be outlined, one for the place of the third Kantian Critique in Heidegger’s work and another for the aesthetics in general and the Kantian aesthetic in particular.